Indentation size and loading rate sensitivities on mechanical properties and creep behavior of solid bitumen - Yuke Liu; Yongqiang Xiong; Kouqi Liu; Chao Yang; Pingan Peng (International Journal of Coal Geology, 2019)
Creep behavior of rocks could impair fracture conductivity and wellbore stability during gas production from highly matured organic-rich shales in South China, of which the organic matter is mainly in the form as solid bitumen and is thought to be a major contributor for the creep deformation. To get a better insight into this phenomenon, this paper for the first time characterizes the mechanical properties and creep behavior of a millimeter-sized solid bitumen sample by using quasi-static state creep tests and Dynamic Mechanical Analysis in nanoindentation, and reports their dependences on indentation size and loading rate, respectively. Mechanical properties (including hardness and Young's modulus) are found to be negatively related with both indentation size and loading rate. The extremely small creep strain rate sensitivity (m) of solid bitumen indicates a localized shear flow inside. And m exhibits slightly positive dependences on indentation size and loading rate. The potential mechanisms controlling the deformation of solid bitumen under indentation are also discussed.
Keywords: Creep; Mechanical properties; Nanoindentation; Solid bitumen